Higher Education Student’s Reflection on Self-Directed Learning During the Online Reading Comprehension - Angraini, Resti; Anita Fatimatul Laeli; Kristi Nuraini (JELP Journal of English Language and Pedagogy, 2025)
In this research, the problem is "how do students reflect on self-directed learning during the online reading comprehension context and the objective of this research referring to the research problem is to investigate students' reflection on selfdirected learning during the online reading comprehension context. Based on the research problem and relevant theory, the hypothesis of this research is described as follow: Students find self-directed learning during the online reading comprehension context help them in learning. The findings in this study show a highly positive response based on nine aspects of perception: online reading proficiency, online discussion proficiency, comprehension competence, technical proficiency, assignment management, procrastination management, stress management, examination management, and time management. Based on the data, 8-42 respondents (17%%-84%%) gave positive responses. This means that independent learning can improve their reading ability. This means that students' reflection on independent learning in online reading content is good for improving reading skills, task management, time management, and learning management